2017
DOI: 10.21608/jappmu.2017.45859
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Some Blood Constituents of Calves Produced From Primi- and Multi-Parous Friesian Cows Fed Yeast Culture

Abstract: This study was conducted to evaluate the effect of dietary supplementation of dairy cows with yeast culture (YC) on immune transfer to their calves during first days after birth and on some blood constituents of calves from birth to 15 wk of age. Total of 15 Friesian cows (weighing 500-520 kg and 2-4 parities) and 15 Friesian heifers (weighing 400-420 kg) at late pregnancy (3 mo pre-partum) were used in this study. All experimental animals were randomly allocated in randomized design to three experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Also, Amer and Badr (2008) concluded that buffalo-cows immunostimulated with levamisole had the greatest levels of IgA and IgG in colostrum compared with non-stimulated buffalo-cows. Our findings were supported by Murphy et al (2005) and Wafa (2017), who indicated that the amount of all immunoglobulin (Ig) fractions in colostrum of buffalo-cows depend mainly upon pre-partum administration of immunepotentiators to dams.…”
Section: Humoral Immune Response Of Damssupporting
confidence: 89%
See 2 more Smart Citations
“…Also, Amer and Badr (2008) concluded that buffalo-cows immunostimulated with levamisole had the greatest levels of IgA and IgG in colostrum compared with non-stimulated buffalo-cows. Our findings were supported by Murphy et al (2005) and Wafa (2017), who indicated that the amount of all immunoglobulin (Ig) fractions in colostrum of buffalo-cows depend mainly upon pre-partum administration of immunepotentiators to dams.…”
Section: Humoral Immune Response Of Damssupporting
confidence: 89%
“…The observed increase in immunoglobulins, IgA, IgM and IgG concentrations in plasma of calves from dams with different treatments was mainly related to enhanced levels of immunoglobulins in colostrum of their dams, particularly those treated with Se-Met+LEV together (Table 4). Similar trend was reported by Murphy et al (2005) and Wafa (2017). Jezek et al (2012) found that quality of colostrum was positively correlated with the levels of IgM, IgA and IgG in the calves' serum in the first week and with the IgG in the fourth week of life.…”
Section: Humoral Immune Response Of Calvessupporting
confidence: 84%
See 1 more Smart Citation
“…However, some authors found that YC supplementation of primiparous and multiparous Friesian cows had no significant effect on calf birth weight (Mostafa et al, 2014). The obtained results in this study indicated heavier birth weight calves in all groups of dams treated with YC, LB or their combination than in the group fed with the control diet, which may be attributed to the improvement in overall health status and weight of their dams (Wafa, 2017). In this way, the concentration of immunoglobulins (IgG, IgA, and IgM) increased in calf blood plasma or their dams colostrum of treatment groups as compared to control, being the highest in calf plasma and colostrum in G4 (YC + LB).The observed significant drop (P<0.05) in IgG level in colostrum on the 2nd day reflected insignificant (P<0.05) reduction in calf plasma IgG on the 3rd day.…”
Section: Discussionmentioning
confidence: 50%
“…Lactobacillus acidophilus is one of the dominant lactobacilli in the human intestine was widely used as probiotic cultures (Oh et al, 2000). In the literature, several reports indicated positive impact of probiotic cultures on performance and production of cattle, in terms of improving feed intake (Ayad et al, 2013), feed efficiency, growth performance (Lascano et al, 2009), nutrient digestibility coefficients (Wohlt et al, 1991), blood hematology (Agazzi et al, 2014) absorption of some minerals (Cole et al, 1992), metabolic health (Dolezal et al, 2012), mucosal immune system function, and levels of immunoglobulin (Heinrichs et al, 2009), when yeast culture was fed to cattle as well as performance of their calves at birth and during the suckling period (Wafa, 2017). However, some authors found that YC supplementation of primiparous and multiparous Friesian cows had no significant effect on calf birth weight (Mostafa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%